Analisis Kebijakan Publik Terhadap Formalisasi Pondok Pesantren di Indonesia - Farhanudin Sholeh (Qolamuna : Jurnal Studi Islam, 2022)
This article discusses the formalization of Islamic boarding school education in policy in Indonesia. The results of the study concluded that Law Number 20 of 2003 in Article 30 paragraph 4, which mentions Islamic boarding schools as religious education, then further regulated in PP Number 55 of 2007 concerning Religious Education and Religious Education in Article 26 paragraphs 1, 2 and 3 and the latest the promulgation of PMA Number 13 of 2014 concerning Islamic Religious Education. In PMA Number 13 of 2014, pesantren are explained in Chapter III of Islamic boarding schools starting from article 26 to article 41. Law Number 18 of 2019 concerning Islamic Boarding Schools further strengthens the existence of pesantren by providing pesantren with endowment funds from the government. Keywords; Formalization, public policy, Islamic boarding school